THE EFFECT OF DETERMINANTS OF CAPITAL STRUCTURE ON STOCK PERFORMANCE IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Jumriah Basri, Jumriah Basri; Nur Eva Yanti, Nur Eva Yanti; A. Kartini Sari Putri D, A. Kartini Sari Putri D (Universitas Ichsan Sidenreng Rappang, 2023)
The Effect of Capital Structure Determinants on Stock Performance in Manufacturing Companies Listed on the Indonesia Stock Exchange. This study aims to determine the effect of profitability, asset structure, and company size on stock performance in manufacturing companies listed on the Indonesia Stock Exchange. The analytical method used in this research is descriptive quantitative method, multiple linear analysis, t test, F test, and classical assumption test with the help of the Social Sciences Statistics Program (SPPS version 21.00). The results showed that the profitability variable had no significant positive effect on stock performance, asset structure had a significant negative effect on stock performance, and company size partially had a significant positive effect on stock performance. Simultaneously the independent variables (profitability, asset structure, and firm size) have a significant and significant effect on the dependent variable (stock performance).